MICROFACIES AND SPHINCTOZOAN ASSEMBLAGE OF SOME LOWER PERMIAN BRECCIAS FROM THE LERCARA FORMATION (SICILY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Some paleozoic calcareous blocks characterized by a rich fossil association, never described before, have been found as elements of the breccias resedimented in the siliciclastic deposits of the Lercara Formation (Western Sicily). These blocks occur in the Cozzo Intronata area (Lercara) and along the River San Filippo (Roccapalumba) mixed with the already known ?Carboniferous calcareous breccias with productid.The sponge-Tubiphytes boundstone and the algal foraminiferal grainstone/packstone are the two main lithofacies types of these new discovered elements. Their Lower Permian age is supported by fusulinids and algae. They probably derived from the dismantling of a carbonate platform margin.The present paper, besides describing the sedimentological and paleontological features of these deposits, is particularly devoted to the systematic study of the sphinctozoan sponges that played an important role as framebuilder organisms of the reef limestones together with the abundant inozoans.10 species are here described. Girtyocoelia beedei (Girty) and Sollasia ostiolata Steinmann are the most frequent species. Other species are rare. A new genus (Parauvanella) and a new species (Cystauletes lercarensis) are introduced.
Keywords: Sphinctozoa; Systematic; Microfacies; Lercara Formation; Lower Permian; Western Sicily.